2022
DOI: 10.1155/2022/6071514
|View full text |Cite
|
Sign up to set email alerts
|

Coal Facies and Its Effects on Pore Characteristics of the Late Permian Longtan Coal, Western Guizhou, China

Abstract: The coal facies and their effects on the coal pore characteristics of the Late Permian Longtan Formation, western Guizhou, were studied, using diverse experiments of macerals and minerals compositions, vitrinite reflectance, and pore characteristics. The results show that five coal facies exist in studied samples, and they are shallow-water covered forest peat swamp facies, moist forest peat swamp facies, dry forest peat swamp facies, low peat swamp facies, and wet land herbaceous peat swamp facies. Among them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The study shows that the development of seepage pores is controlled by the coal phase under similar coalification conditions. Lou et al 17 indicate that the shallow-water-covered forest peat swamp facies exhibit higher porosity and larger pore size, thereby emphasizing the coal facies’ control of a key role in the reservoir pore structure of coal, which, in this study, influences of pore size distribution more clearly than coal rank. Zhao et al 10 reported a bimodal pattern in the pore structure of the wetland forest swamp facies in the eastern Ordos basin featuring well-developed micropores and poorly developed macropores.…”
Section: Introductionmentioning
confidence: 53%
“…The study shows that the development of seepage pores is controlled by the coal phase under similar coalification conditions. Lou et al 17 indicate that the shallow-water-covered forest peat swamp facies exhibit higher porosity and larger pore size, thereby emphasizing the coal facies’ control of a key role in the reservoir pore structure of coal, which, in this study, influences of pore size distribution more clearly than coal rank. Zhao et al 10 reported a bimodal pattern in the pore structure of the wetland forest swamp facies in the eastern Ordos basin featuring well-developed micropores and poorly developed macropores.…”
Section: Introductionmentioning
confidence: 53%
“…A high GI value indicates a wetter coal-forming environment and deeper water cover [44]. The TPI reflects the degree of preservation and degradation, and the higher the TPI value, the better the preservation degree of plant cells, which can be used to determine the type of coal-forming plant [14,45]. The GI and TPI indexes are modified based on Diessel [11] and Jiu et al [46] as follows: GI = (Total Vitrinite + Macrinite)/(Fusinite + Semifusinite + Inertodetrinite) TPI = (Telinite + Telocollinite + Fusinite + Semifusinite)/(Collodetrinite + Macrinite + Inertodetrinite + Vitrodetrinite)…”
Section: Coal Facies Interpretationmentioning
confidence: 99%
“…However, the impact of the peatland environment on coal formation has not been considered. Coal facies contain different combinations of maceral components, and the study of coal facies mainly focuses on the sedimentary environment of coal formation, including coal-forming plants, redox conditions, water activity, pH value, and coal pore structure [10][11][12][13][14][15][16]. Minerals are the major hosts of the vast majority of elements present in coal, such as rare earth elements generally associated with clay minerals, while other trace elements are often associated with pyrite, clay minerals, and many other minerals [17,18].…”
Section: Introductionmentioning
confidence: 99%